Strategies to control dental plaque biofilms- a review - CHANDINI RAVIKUMAR; DR. RADHIKA ARJUNKUMAR (International Journal of Pharma and Bio Sciences, 2017)
Periodontal disease is a highly prevalent infection that affects the human dentition and mainly characterised by extensive inflammation and destruction of the alveolar bone. Bacterial plaque is known to be the most common aetiology of periodontal disease. Many theories have been put forward that aims to describe the pathogenesis of periodontal diseases. Eliminating plaque and preventing its formation continues to be the mainstay of periodontal therapy. It should also be learnt that not all bacteria are harmful.There is a balance between the commensals and the pathogenic bacteria that gets shifted more toward the pathogenic bacteria in disease. The various physiologic, therapeutic and novel strategies that are carried out to combat the plaque biofilms are also discussed in this review.